Pengaruh Citra Merek Dan Kualitas Produk Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening Pada Smartphone Iphone (Studi Kasus Pada Mahasiswa UPI) - Fajar; Yulasmi; Dodi Suryadi (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research aims to determine and attempt to analyze the influence of brand image and product quality on customer loyalty with customer satisfaction as an intervening variable on iPhone smartphones (case study of UPI students). This research is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample of this research are UPI "YPTK" Padang Management Students. The research results found that there is an influence between Brand Image and Customer Satisfaction. Where the P-Value value is (0.001 < 0.05) and the t-statistic value is (3.422 > 1.96). There is an influence between Product Quality and Customer Satisfaction. Where the P-Value value is (0.008 < 0.05) and the t-statistic value is (2.659 > 1.96). There is an influence between Brand Image and Customer Loyalty. Where the P-Value value is (0.043 < 0.05) and the t-statistic value is (2.030 > 1.96). There is no influence between Product Quality and Customer Loyalty. Where the P-Value value is (0.978 > 0.05) and the t-statistic value is (0.028 < 1.96). There is a relationship between Customer Satisfaction and Customer Loyalty. Where the P-Value value is (0.000 < 0.05) and the t-statistic value is (3.933 > 1.96). Customer Satisfaction mediates Brand Image on Customer Loyalty. Where the P-Value value is (0.021 < 0.05) and the t-statistic value is (2.307 > 1.96). Customer Satisfaction mediates Product Quality on Customer Loyalty. Where the P-Value value is (0.023 < 0.05) and the t-statistic value is (2.283 > 1.96).